Determinants of elite rowing performance : implications for developing rowers - Homer, M. R. (Liverpool John Moores University, 2019)
Olympic Rowing is a `power endurance` sport with a range of anthropometric, physiological and technical requirements. Literature examining the physiological determinants of elite rowing performance has rarely included the analysis of different groups or their longitudinal development. Elite rowing traditionally adopts a `squad based` approach to training which often fails to recognise the potential benefits of individualised training. To date, limited data exist examining the individualised profiling of elite rowers leading to the inclusion of bespoke training prescription in order to maximise performance. Study 1 investigated the relationship between 2,000m ergometer performance and regularly monitored physiological variables, which contribute to selection, in male and female elite senior and development rowers. Analysed individually, there were large differences in the relationships observed across gender and competitive level, with submaximal aerobic capacity (power at 4 mmol·l-1 lactate; W4mmol·l -1) being the only variable to significantly correlate with 2,000m performance in all squads. Results were further analysed using bivariate regression to examine the degree of shared variance between physiological status and performance. W4mmol·l -1 was able to explain 25-59% of the variation in performance. Other variables were able to explain the variance in performance to differing degrees, depending on the squad. This suggests that coaches and practitioners should examine performance determinants of homogenous groups, as the determinants of performance may be different depending on gender and competitive level. Study 2 investigated the importance of W4mmol·l -1 by tracking its longitudinal development in a large group of elite male rowers completing the same training programme. Changes in W4mmol·l -1 were analysed in order to investigate progression rates and differences between Olympians (OLY) and non-Olympians (NON). OLY improved significantly following each of the first 3 years of elite level training. The results of a case series analysis of individual athletes, including a double Olympic gold medallist with >12 years of international experience, suggested a clear upward trend in W4mmol·l -1 throughout a career, despite fluctuations within individual seasons and Olympiads. Improvements were attributed to the physiological adaptations associated with a consistent and well executed high volume/low intensity training model. Differences in the development of W4mmol·l -1 between OLY and NON were not significant until the 3rd year of elite level training. The stagnation in W4mmol·l -1 observed in NON athletes at this time was ascribed to a ceiling of aerobic development or an inability to effectively polarise training in order to maximise adaptation. At this point alternative training methods could be introduced in order to avoid stagnation in development and subsequent performance. Physiological profiling during the early stages of an athlete`s career could also identify those more likely to thrive in a high volume/low intensity training programme. Study 3 involved the implementation of a physiological `Spider Profile` for club rowing coaches. Using key performance determinants, development athlete`s relative strengths were identified in order to inform the training process. Results were compared to senior athletes and `Olympian Standards`. U23 international athletes possessed significantly greater maximal and sub-maximal `rowing specific` endurance capacities than noninternational rowers, and were significantly weaker than senior athletes in measures of maximal strength. It was therefore suggested that in order to improve their chances of U23 and senior team selection, development athletes should prioritise the improvement of technical and aerobic indices of performance rather than strength and power. Also, the identification of new athletes should be weighted more towards endurance factors than maximal strength and power production. Study 4 refined the physiological profiling system developed in the previous studies and used it to implement training interventions that improved individual weakness in a group of six elite male rowers. Athletes were assigned to either an endurance (END, N=4) or maximal power (MAX, N=2) group depending on the results of a complete physiological profile. All rowers completed a generic rowing training programme (mean volume = 131 km per week) with 2 of the 14 sessions per week comprising either high intensity aerobic interval training or additional weight lifting. Results were analysed as a case series with individual responses discussed as a lack of control group made the relative impact of training interventions difficult to assess. Three out of four END athletes improved aerobic indices, in particular V&O2peak, but made no improvements in markers of power production. MAX athletes improved their maximum power and aerobic performance. This was attributed to increased mechanical efficiency, muscle coordination and recruitment, strength related technical improvements and/or the reduced relative intensity of sub-maximal work leading to conservation of energy. In conclusion, the minor adaptation of a generic rowing training programme can have a marked effect on the physiological adaptation of athletes struggling to make progress in a traditional high-volume/low-intensity system. In summary, this thesis has highlighted that the analysis of heterogeneous groups of rowers does not provide the level of detail necessary to describe elite performance. Instead, due to individual differences in determinants of performance, a case series approach is a more appropriate means of identifying strengths and weaknesses and implementing interventions to make improvements. Aerobic indices of performance are highlighted as the most important descriptors at both a development and international level. In particular sub-maximal capacity, which is superior in elite development athletes, can be used to differentiate between those that achieve senior team selection, Olympic success, and those that fail to reach the upper echelons of the sport. Spider Profiles are an effective tool which highlight individual strengths and weaknesses in development athletes. Such profiles can be used to provide bespoke interventions to individuals failing to make an impact in elite rowing teams, and the subsequent improvements made can have a global effect on performance if they can be applied to the rowing stroke effectively.